The Mông Sơn Thí Thực Ritual in the Context of Contemporary Vietnamese Culture: Social Role, Spiritual Significance, and Cultural Value - Khang, Nguyen Tan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
The Mông Sơn Thí Thực ritual, an integral practice within Northern Buddhism in Vietnam, has transformed from a religious rite into a dynamic cultural and social phenomenon. This study investigates the ritual’s social functions, spiritual significance, and cultural value in the context of contemporary Ho Chi Minh City—a space marked by urbanization, religious pluralism, and shifting moral frameworks. Anchored in an interdisciplinary framework that draws from Vietnam Studies, cultural studies, anthropology, religious sociology, and Buddhist studies, the research employs a mixed-methods approach. Qualitative data were collected through participant observation and in-depth interviews with monks, nuns, and lay Buddhists at temples, home altars, and large-scale Buddhist ceremonies. These narratives were analyzed thematically to capture diverse perceptions and lived experiences surrounding the ritual. Quantitative data were gathered through a structured survey involving 800 respondents (400 monastics and 400 laypeople). The sample was determined using Yamane’s formula, with data analyzed via descriptive statistics. Findings indicate that the ritual fulfills several interrelated roles: it acts as a spiritual offering to forgotten souls, a moral training space for cultivating compassion and filial piety, and a platform for reinforcing collective identity and cultural continuity. Moreover, the ritual provides psychological relief for participants, functioning as a form of collective spiritual therapy amidst the anxieties of modern life. This study contributes new insights into how Buddhist ritual practices in Vietnam adapt to contemporary contexts. It highlights the enduring relevance of religious traditions as resources for moral resilience, cultural transmission, and social cohesion in an increasingly fragmented world.